Temporal trends, short- and long-term prognostic impact of pre-hospital delay times in ST elevation myocardial infarction – 20 years national data from the SWEDEHEART registry. (3rd October 2022) - Ericsson, M; Alfredsson, J; Thylen, I; Stromberg, A; Sederholm Lawesson, S
Abstract: Background: Previous studies have demonstrated that total ischaemic time during ST-elevation myocardial Infarction (STEMI) is associated with mortality. However, how duration from symptom onset to hospital admission affects outcomes and how pre-hospital delay times (PHDT) have evolved over time in STEMI in total, as well as in prespecified subgroups, remains unknown. Aim: The aim was to explore temporal trends and prognostic impact of PHDT in STEMI patients during the last two decades in Sweden, including the fibrinolytic era as well as the primary percutaneous coronary intervention (PPCI) era. Temporal trends of PHDT was aimed to be studied in the total STEMI cohort as well as in subgroups according to age, sex and presence or absence of diabetes. Method: This was an observational retrospective cohort study based on the SWEDEHEART registry including 89, 155 STEMI patients between 1998 and 2017. Results: In total, the PHDT curve was hump-shaped without any significant trend. The median PHDT was 150 min (Q1 80; Q3 302), and the shortest PHDT of 140 (Q1 85; Q3 274) min was found during the last period. During the fibrinolytic era (1998–2004) there was a significant increase in PHDT while delay times decreased during the PPCI era (2005–2017). There were consistent differences within subgroups; women sought care 25 min later than men, older (>70 years) delayed 30 min longer than younger and patients with diabetes 29 min longer than those without. Higher short- and long-term mortality was seen with increasing delay except for the group seeking care within 1 hour, which had higher short-term mortality. In five years follow up, mortality incrementally increased with delay, from 24.1% (0–1 hours) to 31.1% (>12 hours) of PHDT, p<0.01. When adjusting for confounders the risk of dying within 1 and 5 years was approximately 1% per hour of increase of PHDT (HR 1.011, 95% CI 1.006–1.016 and HR 1.008, 95% CI 1.004–1.013, respectively). Conclusions: PHDT is an independent predictor of short- and long-term mortality and reducing PHDT will diminish the risk of heart failure and premature death. We found only a modest decrease in PHDT over time and the trend was hump shaped. Since the implementation of PPCI, with the diagnosis of STEMI made in the ambulances, these have been redirected in the pre-hospital setting, transporting the patient directly to cath lab. This may explain why the PHDT initially increased in the beginning of this era when new routines were being established. Although we did not find any significant trend during the total 20-year period it is reassuring that the PHDT decreased during the PPCI era. Anyhow, there are subgroups with consistently prolonged PHDT, such as women, the elderly, and patients with diabetes, who need to be targeted in future interventions. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): This study was funded with grants from the Medical Research Council of Southeast Sweden (FORSS), Region Östergötland and Linköping University Hospital Research Fund, Sweden.